A dimensão ambiental no desenvolvimento profissional de professores e professoras das escolas rurais - Zakrzevski, Sônia Beatris Balvedi (Universidade Federal de São Carlos, 2002)
This work aims to reflect on the continued formation in Environmental Education of rural school teachers. In recovering the story of education in rural environment, the research highlights the negligence with the education in this environment and the lack of research and intervention in Environmental Education turned into the population of the field, a marginalized and forgotten people, who is suffering the impacts of the Brazilian rural development model, generator of several economical, social and ecological problems. It aims to discuss the insertion of Environmental Education in school curriculums, and in reflecting about the main tendencies of it, rescues its story in gauche school. From the analysis of the main tendencies and approaches in teachers formation, it reports and discusses a research-action (comprehended as a strengthening of the action in the reflection and in the disruption of subject-object to subject-subject, as an incentive to participative autonomy of schooling group for a critical incorporation of Environmental Education in school curriculums), developed in four towns in the north region of the State of Rio Grande do Sul/ Brazil. The work developed with rural teachers reinforced a collective posture and stimulated teachers to make a profound study toward the comprehension of their own practice. The research, an instrument taken from the teachers hands, contributed for the formation of individuals capable to create a different rural world. This research made us to recognize some limitations of the research-action regarding its emancipatory attributes. We concluded that the fact teachers have formed a political conscience; starting to be more active and critical, not always make them autonomous, free to give their work the direction they wish. This thesis is just the beginning of a long debate, which deserves more attention by the people who work in the education field, recognizing it as an essence in the construction of any thought that might contribute for the humane development inserted in environmental contexts.
Keywords: Educação ambiental; Professores formação; Educação rural; Pesquisa ação em educação; Currículos; Meio ambiente; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA